THE IMPACT OF THE WRITER SAID AHMED'S WORKS ON THE DEVELOPMENT OF THE UZBEK LANGUAGE AND LITERATURE AND THEIR CHARACTERISTICS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the profound impact of writer Said Ahmed's works on the development of the Uzbek language and literature, shedding light on his unique contributions and their lasting significance. Renowned for his innovative narrative style and thematic breadth, Ahmed's literary creations reflect the social, cultural, and political landscapes of Uzbekistan. The study examines key characteristics of his writing, including linguistic features, stylistic approaches, and thematic concerns, emphasizing how these elements have influenced contemporary Uzbek literature. By analyzing his prominent works, the article aims to illustrate how Said Ahmed not only elevated the Uzbek literary canon but also played a crucial role in the promotion and preservation of the Uzbek language amidst historical challenges. The findings underscore the importance of his legacy in shaping modern Uzbek literature and fostering cultural identity.